Subconjunctival filtration in evolution: current evidence on MicroShunt implantation for treating patients with glaucoma - Iqbal Ike K. Ahmed; Omar Sadruddin; Joseph F. Panarelli (Eye and Vision, 2023)
Abstract Background Although traditional surgical procedures for glaucoma (such as trabeculectomy and tube-shunt implantation) can significantly reduce intraocular pressure (IOP), they are associated with numerous complications, some of which are vision-threatening, or involve prolonged recovery or a highly intensive postoperative course. Micro-invasive glaucoma surgery (MIGS) procedures have shown better safety but reduced efficacy in achieving target IOP. Combinations of these methods have led to the development of subconjunctival micro-invasive procedures with safety comparable to traditional surgery and greater efficacy than minimally invasive methods. This review describes the use of one of these devices, the poly(styrene-block-isobutylene-block-styrene) (SIBS)-based PreserFlo MicroShunt (Santen, Emeryville, CA), in the surgical treatment of patients with glaucoma. Main text The MicroShunt is an 8.5-mm tube made of an inert polymer with no endplate, an internal diameter of 70 μm, and fins intended to prevent peritubular flow and anchor the device within the sclera to prevent proximal migration into the eye. Following ab externo implantation, the tube provides a conduit for flow of aqueous humor from the anterior chamber into the subconjunctival/sub-Tenon space. Clinical trials to date have shown that, when paired with mitomycin C (MMC) treatment, MicroShunt implantation significantly reduced both IOP and the number of glaucoma medications. These IOP-lowering results were found both when surgery was performed alone and with phacoemulsification. The MicroShunt also showed a safety profile comparable to that of traditional filtering surgery. Conclusions The MicroShunt and other novel subconjunctival procedures have shown substantial IOP reductions while mitigating hypotony-related complications. MMC, which modulates fibrosis and scarring postoperatively, is essential to surgical success. Randomized, long-term clinical trials will further clarify the role of controlled micro-incisional device-assisted ab externo glaucoma filtering surgery in long-term glaucoma management.